Keutamaan Prinsip Fairness dan Publisher Right Dalam Melindungi Perusahaan Media Nasional di Era Disrupsi Digital - Rubben Denova Rohmana; Danrivanto Budhijanto; Laina Rafianti (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
One of the crucial problems in this era of digital disruption is the existence of digital platforms that threaten the sustainability of local media companies in Indonesia. One of the important things to study is the existence of effective legal regulations to overcome these problems. In this study, the method used was a statutory approach with specifications that were descriptive analytical. This research found that basically, there are currently several settings in Indonesia related to news media content. However, these arrangements are seen as not maximally protecting local media companies. The results of this study show that Indonesia has not been optimal in protecting local media companies, especially regarding the relationship between local media companies and digital platforms that are increasingly asymmetrical. Therefore, specific legal regulations are needed in Indonesia, which can balance the bargaining position between the two parties and can prioritize the principle of fairness and publisher right. If these problems are not addressed immediately, the sustainability of local media companies in Indonesia will be further threatened.